Collaborative framework for virtual organisation synthesis based on a dynamic multi-criteria decision model - Arrais-Castro, Antonio (2018)
Globalisation and increased competition pushes companies to grow outside political and geographical boundaries, frequently forcing them to increase product diversification and optimise their relation with potential and effective partners and customers. In this scenario, implementing agile collaboration networks with business partners is a requirement. In this article the authors propose a collaborative framework based on a model for Historical, Present and Future evaluations, which in turn is based on a Dynamic Multi-criteria Decision Method using software agents and the Cloud for Collaborative Networked and Virtual Organization Synthesis. The model uses a dynamic decision approach for supplier and business partner evaluation, enabling software agents to autonomously capture business opportunities, select business partners/suppliers, award and process associated orders.